The Impact of Nanoparticles and Aging on AC Dielectric Strength of Nomex Polymeric Composite: Weibull Distribution Based Analysis - Maity, Soumyadeep; Paul, Sandipan Kumar; Chakraborty, Biswajit; Maur, Subhajit; Pradhan, Arpan Kumar; Dalai, Sovan; Chatterjee, Biswendu; Chatterjee, Saibal (Engineering, Technology & Applied Science Research, 2025)
This research investigated the influence of insulating (Al2O3), semiconducting (TiO2), and conducting (Fe3O4) Nanoparticles (NPs) on the breakdown strength of Nomex-based polymeric Nanocomposites (NCs). Seven samples were fabricated and thermally aged at 145 °C for 600 h to simulate accelerated degradation. Fourier Transform Infrared Spectroscopy (FTIR) was conducted to unaged, 300 h, and 600 h aging durations to examine the chemical alteration and understand the NP-induced resistance of meta-aramid polymeric chains against the thermal aging. The AC Breakdown Voltage (ACBDV) was measured every 100 h of aging, and the results were analyzed using the Weibull distribution to extract the scale parameters, shape parameters, and p-values. Cumulative breakdown probabilities at 1%, 10%, and 50% risk levels were evaluated to assess the impact of different NPs on the breakdown mechanism. After 600 h of aging, the incorporation of 1 wt% Al2O3 improved the BDV of pristine Nomex by 28.2%. At a 50% risk probability, BDV enhancements of 63.16% (Al2O3), 48.89% (TiO2), and 42.39% (Fe3O4) were achieved, demonstrating the superior performance of NP-reinforced Nomex insulation under thermal stress..